Analyzing Students’ Perception of Speaking Problems and Mispronunciation At English Department UIGM - Karunia Karunia; Retika Wista Anggraini; Rudi Hartono (Universitas Indo Global Mandiri, 2019)
AbstractThis research aimed to identify the problems of speaking of sixth semester students of English Department UIGM based on their opinion, to reveal kinds of speaking activities that sixth semester students of English Department UIGM hope to be included in speaking courses, and to reveal how many mispronunciation errors that they made during the interview. The type of this research was descriptive research. The participants of the research were the four sixth semester students of English Department UIGM. The instrument used was interview. The result of the analysis showed that the participants have problems in speaking which are divided into two major problems; psychological and linguistic problems. The psychological problems include feeling nervous and being afraid to speak in English in front of the class. The second major problem is linguistic problems, which include problems in speaking aspects like pronunciation, grammar, and vocabulary. The participants suggested four activities that they hope to be included in speaking courses; singing, English speaking day, speaking with native speaker, and being an international event volunteer. The last, the participants mispronunced 30 English words which consists of vowels (/a/, /ə/, /e/, and /æ/), consonants (/ʃ/, /k/, /Ө/, and /v/) and diphthongs (/aʊ/ and /ɪə/).Keywords : Students’ Perception, Speaking, Mispronunciation, EnglishAbstrakPenelitian ini bertujan untuk mengidentifikasi berbagai masalah dalam berbicara yang dihadapi oleh mahasiswi-mahasiswi semester enam Program Studi Bahasa Inggris UIGM berdasarkan opini mereka, untuk mengungkap macam-macam aktivitas berbicara yang mereka harap dapat disertakan dalam mata kuliah speaking, dan untuk mengungkap berapa banyak kesalahan pengucapan yang mereka buat selama wawancara. Jenis penelitian ini adalah penelitian kualitatif. Partisipan-partisipan dari penelitian ini adalah empat mahasiswi semester enam Program Studi Bahasa Inggris UIGM. Instrumen yang digunakan adalah wawancara. Hasil dari analisa menunjukkan bahwa para partisipan memiliki masalah dalam berbicara yang terbagi dalam 2 macam inti masalah; masalah-masalah psikologis dan masalah-masalah kebahasaan. Masalah-masalah psikologis meliputi perasaan gugup dan takut untuk berbicara menggunakan bahasa Inggris di depan kelas. Masalah kedua adalah masalah-masalah kebahasaan, yang meliputi masalah dalam unsur-unsur berbicara seperti pengucapan, tata bahasa, dan kosakata. Para partisipan menyarankan empat aktivitas yang mereka harap dapat disertakan dalam mata kuliah speaking; menyanyi, hari berbahasa Inggris, bercakap-cakap dengan penutur asli bahasa Inggris, dan menjadi panitia acara internasional. Terakhir, para partisipan keliru dalam mengucapkan 30 kata berbahasa Inggris yang mengandung huruf vokal (/a/, /ə/, /e/, and /æ/), konsonan (/ʃ/, /k/, /Ө/, and /v/) dan diftong (/aʊ/ and /ɪə/).Kata kunci : Persepsi Mahasiswa, Berbicara, Kesalahan Pengucapan, Bahasa Inggris